2017
DOI: 10.3892/ijmm.2017.3115
|View full text |Cite
|
Sign up to set email alerts
|

Histone lysine methylation and congenital heart disease: From bench to bedside (Review)

Abstract: Histone post-translational modifications (PTM) as one of the key epigenetic regulatory mechanisms that plays critical role in various biological processes, including regulating chromatin structure dynamics and gene expression. Histone lysine methyltransferase contributes to the establishment and maintenance of differential histone methylation status, which can recognize histone methylated sites and build an association between these modifications and their downstream processes. Recently, it was found that abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 171 publications
(179 reference statements)
1
17
0
Order By: Relevance
“…SMYD proteins in mammals are located in both the cytoplasm and the nucleus, and correspondingly have the ability to methylate both histone and non-histone targets (Brown et al 2006;Gottlieb et al 2002;Hamamoto et al 2004;Huang et al 2006;Mazur et al 2014;Tracy et al 2018;Yi et al 2017). SMYD1 was also detected in both the cytoplasm and the macronucleus (and possibly micronucleus) in Tetrahymena cells, which is consistent with its localization in mammalian systems.…”
Section: Smyd Is Involved In the Regulation Of Metabolism-related Gensupporting
confidence: 72%
“…SMYD proteins in mammals are located in both the cytoplasm and the nucleus, and correspondingly have the ability to methylate both histone and non-histone targets (Brown et al 2006;Gottlieb et al 2002;Hamamoto et al 2004;Huang et al 2006;Mazur et al 2014;Tracy et al 2018;Yi et al 2017). SMYD1 was also detected in both the cytoplasm and the macronucleus (and possibly micronucleus) in Tetrahymena cells, which is consistent with its localization in mammalian systems.…”
Section: Smyd Is Involved In the Regulation Of Metabolism-related Gensupporting
confidence: 72%
“…Previous research has shown that both HMTs and histone demethyltransferases may be implicated in CHD pathogenesis . However, evidence of HMT involvement in alcohol‐induced CHD development is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…To date, researchers have conducted extensive investigations on cardiovascular disease at the genetic and epigenetic levels, and these studies have greatly deepened our understanding of cardiovascular disease [4][5][6][7][8][9][10][11]. Most conventional therapies available for patients with cardiovascular disease involve protein-targeting drugs.…”
Section: Introductionmentioning
confidence: 99%